Reformulation of People's Market Management in Pinrang Regency - Hasim, Hasanuddin; Pradana, Syafa'at Anugrah; Pikahulan, Rustam Magun; Rahman, Aulia Audri; Reska, Nurul Alfita (Al-'Adl, 2024)
The establishment of regional regulations on people's market management aims to create a well-functioning market environment, provide benefits to traders, consumers, and the wider community, and support the overall economic growth of the region. With good regulation, it is hoped that the people's market can become a competitive economic center, while ensuring welfare for all parties involved. The method used in this study is empirical juridical where this method applies legal knowledge theoretically and applies it in real situations or contexts, for testing, evaluation, and refinement of the legal system. The results showed that of the 21 people's markets in Pinrang Regency, there were only 3 people's markets that almost met the standardization of people's market facilities and infrastructure, namely Pinrang Main Market, Kariango Market, and Pekkabata Market. While the other 18 markets do not meet the standards of people's market management. Therefore, this study provides academic analysis in reformulating academic manuscripts  in the formation of regional regulations on the management of people's markets in Pinrang Regency as a form of legal certainty and justice in terms of theoretical, sociological, and juridical aspects.